Low-cost options for pathogen reduction and nutrient recovery from faecal sludge - Koné, D.; Cofie, Olufunke O.; Nelson, K. (2010)
Recently, the application of excreta-based fertilizers has attracted attention due to the strongly increasing prices of chemically produced fertilizers. Faecal sludge from on-site sanitation systems is rich in nutrients and organic matter, constituents which contribute to replenishing the humus layer and soil nutrient reservoir and to improving soil structure and water-holding capacity. Hence, it represents an important resource for enhancing soil productivity on a sustainable basis. However, there is little in the scientific literature about the performance of treatment technology allowing recovery of nutrient resources from human waste. This paper reviews the state of knowledge of different processes that have been applied worldwide. Their pathogen removal efficiency as well as nutrient and biosolids recovery performances are assessed. The chapter outlines the gaps in research for further development.